Circuit training improves physiological conditions among wheelchair basket players - Francesco Tafuri; Rosabel Martinez-Roig; Hendra Setyawan; Nugroho Susanto; Khoiril Anam; Emma Saraiello; Umberto Avino; Francesca Latino (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The utilization of a wheelchair exclusively has a profound impact on an individual's musculoskeletal, metabolic, and cardiorespiratory functions. Various programs focusing on physical activity intervention have proven to effectively enhance these physiological responses in wheelchair users. Nevertheless, there has been a limited number of studies investigating the impact of a circuit training physical activity adaptive program on improving these parameters in wheelchair basketball participants. Therefore, the primary aim of this research was to evaluate and identify alterations in cardiorespiratory fitness and musculoskeletal strength among wheelchair basketball players following a circuit training intervention. The study involved 36 male wheelchair basketball athletes with spinal cord injuries aged between 19 and 26 years. They were divided into an experimental group participating in a circuit training program [EG, n = 18], and a control group undergoing exclusively aerobic upper-body exercise training [CG, n = 18]. Anthropometric measurements and the 12-minute wheelchair propulsion distance test, which evaluates the maximal oxygen uptake (VO2max), were conducted for all participants at the commencement and conclusion of the training period. The results demonstrated a significant interaction between Time and Group for the 12-minute wheelchair propulsion distance variable, indicating a notable improvement in the intervention group (p < 0.001). Conversely, no significant changes were observed in the control group. Hence, the findings suggest that incorporating circuit training exercises into the daily training regimen can have a substantial positive influence on the cardiorespiratory fitness and musculoskeletal strength of wheelchair basketball players.